Analisis Risiko Goliath Crane Galangan Kapal Menggunakan Fuzzy FMEA - Bachtiar, Ilham Bima; Darul K., Mades; Yusuf S., Mochamad (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Perkapalan Negeri Surabaya, 2024)
The Goliath crane is a very vital machine for the shipbuilding industry because of its lifting capacity which supports the ship production process, especially in the block erection process. The problem that often occurs with the goliath crane is when the engine fails and cannot be used so that the ship production process stops. Although according to the company's failure data there are no component failures that can cause work accidents, it is important to carry out a risk analysis because the size of the crane and the weight of the erection block being lifted can cause work accidents. The results of the analysis using fuzzy FMEA in longtravel mechanism of a goliath crane show that there are three failures that have a high medium to low high risk level where the FRPN value is more than 7, namely cracks in the crane legs, cracks in the main girder and malfunctioning thruster brakes. The recommendation to overcome this problem is to carry out a visual inspection once a year on the crane legs and main girder and to inspect and check the thruster components for each crane to be used.